P1551FAMILY SUPPORT IS CRUCIAL FOR DIALYSIS PATIENTS TREATMENT ADHERENCE AND QUALITY OF LIFE. (6th June 2020) - Trajcheska, Lada; Rambabova Bushljetikj, Irena; Selim, Gjulsen; Sikole, Aleksandar; Spasovski, Goce; Spasovska Vasilova, Adrijana; Milenkova, Mimoza; Canevska, Aleksandra; Nikolov, Igor
Abstract: Background and Aims: Non-compliant dialysis patients are at increased risk of mortality. Compliance depends on patient demographics, educational level and income. Family support and marital status might also influence the patients compliance, as well as the quality of life. Missed/shortened dialysis sessions, adherence to prescribed medications, excessive phosphate serum values and interdialytic weigh gain, smoking and adherence to medical investigations provide indicators of non-compliance. Aim: To assess the impact of family support on different compliance indicators in the dialysis patients. Method: In this observational study 134 dialysis patients were scored for different indicators of compliance from 0-2 and summary scores of compliance were assessed. Clinical and laboratory data were obtained from the previous two years. Patients with mean IDWGs >4.5% of body weight (BW) and/or phosphorous level above 1.6 mmol/L were scored with 1, patients with IDWG/BW more than 5.7% and/or 2.0 for mean phosphorous level were scored with 2. Summary scores of non-compliance were also assessed. Patients were scored for quality of life with SF-36 questionnaire. Patients non-adherence was analysed for predictors in multivariate analysis. Results: Estimated rates of noncompliance varied: Medical investigations 63%, phosphorous 33, IDWG 22, therapy 14%, HD treatment 9%. When the complete dietary fluid, medications and treatment regimen were studied noncompliance rate was 73%, and when adherence to medical investigations was added the rate rose up to 87%. Patients with family support above median level (≥25) were significantly more often men (0.049), with diabetes (p=0.014), lower socioeconomic status (0.001) and married (0.003). The quality of life scores were significantly worse in the low family supported patients (56.73±26.15 vs 39.23±24.05, p=0.0001). They also scored worse in overall non-compliance scores 2.04±1.71 vs 2.97±2.06, p= 0.007). In the multivariate analysis the non-compliance was predicted most powerfully in patients with younger age, low social status and lower family support (β=-0.202, p=0.023, β=0.220, p=0.036, β=-0.175, p=0.019, respectively). Conclusion: Family support is crucial for dialysis patients adherence to treatment and Quality of life. Efforts should be done to recognize the patients real needs and adequately help those confronting dialysis burden and improve their quality of life.